Demons and healing : the reality of the demonic threat and the Doppelgänger in the light of anthroposophy : demonology, christology and medicine /: the reality of the demonic threat and the Doppelgänger in the light of anthroposophy : demonology, christology and medicine. (2020) - Thoresen, Are Simeon, 1952-
No abstract available